Drug–Drug Interactions and Diagnostics for Drug Users With HIV and HIV/HCV Coinfections: Introduction. Issue 2 (March 2017) - Khalsa, Jag H.; Talal, Andrew H.; Morse, Gene
Abstract: Substance use and pharmacologic treatment of co‐occurring infections such as human immunodeficiency virus (HIV) and hepatitis C virus (HCV) are associated with many adverse consequences including pharmacokinetic and pharmacodynamic drug–drug interactions (DDIs). The National Institute on Drug Abuse sponsored a 2‐day conference on DDIs at which clinicians/scientists from government, academia, and the pharmaceutical industry presented the most current research findings to formulate a comprehensive overview of DDIs. Specific topics discussed included drug metabolism; drug interactions between medications used in the treatment of HIV, HCV, and substance use disorders; intrahepatic concentrations and methods of assessment of drugs in liver disease of varying etiologies and degrees of impairment; and minimally invasive sampling techniques for the assessment of intrahepatic drug concentrations, viral replication, and changes in gene expression in response to treatment. Finally, the speakers identified research targets and priorities on DDIs. Areas of emphasis included development of diagnostic assays for drug concentration assessment in different organs, an enhanced understanding of factors responsible for alterations in drug metabolism and excretion, and establishment of clinical trials and work groups to study DDIs. Our long‐term objective is to broaden investigation in the field of DDIs in substance users.